Intrinsic functional connectivity brain networks mediate effect of age on sociability - Yuet Ruh Dan; Savannah K. H. Siew; Junhong Yu (PLoS ONE, 2025)
Social interaction has been shown to prolong lifespan and healthspan. For older adults living alone, social interaction largely comes from formal social participation, and thus depends on the sociability of the individual. This study aims to understand the effect of age on sociability, and the possible mechanisms behind the change. 196 German participants aged 20–77 (Mage = 37.9) completed a series of questionnaires as part of the Leipzig Study for Mind-Body-Emotion Interactions. Sociability was measured by a subscale of the Trait Emotional Intelligence Questionnaire (Short Form), and network-based statistics were performed on resting-state functional connectivity data to identify networks positively and negatively correlated with age. Mediation analysis was carried out between age and sociability, with both sets of edges as mediators. Overall, age correlated negatively with sociability. The brain network correlating positively with age correlated negatively with sociability, and vice versa for the network correlating negatively with. Both networks independently and completely mediated the age-sociability relationship. The limbic-insular and ventral attention-somatomotor connectivity featured prominently in the age-positive network, while the age-negative network is largely represented by subcortical-parietal and frontoparietal-default mode connections. Networks associated with brain aging can explain the negative relationship between age and sociability. Per Dunbar’s social brain hypothesis, age-related disruption in intrinsic functional connectivity may impair socio-cognitive functions necessary for forming and maintaining relationships, thus causing a decrease in sociability. Psychoeducation of these changes that occur with natural aging could prove useful in the promotion of successful aging.